Respostas

A melhor resposta!
2013-11-22T21:57:56-02:00
28 -
3x - 44 = 2x
3x - 2x = 44
x = 44

29-
A)  2x + 3 = 19
2x = 19 - 3
2x = 16
x = 16 / 8
x = 8

B) 3x - 6 = 12
3x = 12 + 6
3x = 18
x = 18 / 3
x = 6

C)
5x - 7 = 72
5x = 72 + 7
5x = 79
x = 79 / 5
x = 18,8

D) 4x + 15 = 95
4x = 95 - 15
4x = 80
x = 80/4
x = 20

E) 7x - 14 = 70
7x = 84
x = 84 / 7
x = 12

F) 10x - 6 = 144
10x = 144 + 6
10x = 150
x = 150 / 10
x = 15

G) 6x + 1 =97
6x = 96
x = 96 / 6
x = 16

H) 4x - 5 = 135
4x = 135 + 5
4x = 140
x = 140 / 4
x = 35

I) 5x + 18 = 88
5x = 88 - 18
5x = 70
x = 70 / 5
x = 14
1 5 1